1989
DOI: 10.1038/bjc.1989.6
|View full text |Cite
|
Sign up to set email alerts
|

Competitive exclusion of clonal subpopulations in heterogeneous tumours after stromal injury

Abstract: Summary Xenografted artificial heterogeneous tumours (AHTs) were created by admixing, in a ratio of 9:1 or 1:9, two clonal subpopulations (designated as clones A and D) obtained from a heterogeneous human colon adenocarcinoma. In unperturbed AHTs these percentages remain constant with increasing tumour size. At average volumes of 250 mm3, AHTs were X-irradiated (15 Gy) and changes in growth rate and composition assayed. A and D cells exhibited equivalent levels of survival after in vivo irradiation as determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…4 and 8). The existence of these dominant behaviours exhibited by the u 1 or u 2 populations are consistent with the principle of competitive exclusion of clonal sub-populations in heterogeneous tumours (Egan Keats et al, 2012;Leith et al, 1989). In Fisher et al (2013) the authors interpreted the experimental data, which showed suppression and reappearance of cancer clones in myeloma patients (Keats et al, 2012) and chronic lymphocytic leukaemia patients (Schuh et al, 2012), by suggesting that two subclones can exist in a dynamic equilibrium.…”
Section: Conclusion and Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…4 and 8). The existence of these dominant behaviours exhibited by the u 1 or u 2 populations are consistent with the principle of competitive exclusion of clonal sub-populations in heterogeneous tumours (Egan Keats et al, 2012;Leith et al, 1989). In Fisher et al (2013) the authors interpreted the experimental data, which showed suppression and reappearance of cancer clones in myeloma patients (Keats et al, 2012) and chronic lymphocytic leukaemia patients (Schuh et al, 2012), by suggesting that two subclones can exist in a dynamic equilibrium.…”
Section: Conclusion and Discussionmentioning
confidence: 80%
“…Note that these growth functions incorporate also the principle of competition between clonal sub-populations in heterogeneous tumours (Leith et al, 1989).…”
Section: Derivation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation